The University of Zurich (UZH) Hosts the Inaugural Dorothy Crowfoot Hodgkin Symposium - Nathaniel S. Finney (CHIMIA, 2006)
On friday, May 5th, 2006, the Organic Chemistry Institute hosted the inaugural Dorothy Crowfoot Hodgkin symposium at the University of Zurich. The symposium, which will be held annually, will showcase the work of premier female researchers from all scientific disciplines. Dr. Jenny Glusker presented a broad and informative retrospective of Hodgkin's life, after which Prof. Anna Bernardi provided an overview of her group's work in the synthesis and biological evaluation of glycomimetics. Dr. Jennifer Albaneze-Walker described work carried out under her supervision at Merck on the development of PDE IV inhibitors, and Prof. Lia Addadi unified the preceding themes in presenting her work on antibody recognition of cholesterol-related structures.